2020
DOI: 10.1029/2020jb019837
|View full text |Cite
|
Sign up to set email alerts
|

P Wave Tomography Beneath Greenland and Surrounding Regions: 1. Crust and Upper Mantle

Abstract: We study the 3-D P wave velocity (Vp) structure of the crust and upper mantle beneath Greenland and surrounding regions using the latest P wave arrival time data. The Greenland Ice Sheet Monitoring Network (GLISN), initiated in 2009, is an international project for seismic observation in these regions using 34 stations. We use a regional seismic tomography method to simultaneously invert P wave arrival times of local earthquakes and P wave relative traveltime residuals of teleseismic events. These data are ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(60 citation statements)
references
References 89 publications
(203 reference statements)
7
53
0
Order By: Relevance
“…Journal of Geophysical Research: Solid Earth the N-S direction through Iceland, Jan Mayen, and Svalbard obtained by Toyokuni et al (2020) and this study. Toyokuni et al (2020) revealed clear separation of the Iceland, Jan Mayen, and Svalbard plumes in the upper mantle as well as connection of these three plumes in the MTZ, forming a widespread low-Vp anomaly.…”
Section: 1029/2020jb019839supporting
confidence: 50%
See 4 more Smart Citations
“…Journal of Geophysical Research: Solid Earth the N-S direction through Iceland, Jan Mayen, and Svalbard obtained by Toyokuni et al (2020) and this study. Toyokuni et al (2020) revealed clear separation of the Iceland, Jan Mayen, and Svalbard plumes in the upper mantle as well as connection of these three plumes in the MTZ, forming a widespread low-Vp anomaly.…”
Section: 1029/2020jb019839supporting
confidence: 50%
“…In this study, the position of the station SUMG (−38.461°, 72.574°) on the summit of the GrIS is defined as the reference point. The details of the coordinate transformation are given in Appendix A of Toyokuni et al (2020). As a result, the study region is moved to the equatorial region.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations